2022
DOI: 10.1021/acs.jpcc.1c09124
|View full text |Cite
|
Sign up to set email alerts
|

In Operando FTIR Study on the Effect of Sulfur Chain Length in Sulfur Copolymer-Based Li–S Batteries

Abstract: Synthesis of sulfur-rich copolymers using the inverse vulcanization reaction is a practical approach to modify the sulfur active material for enhanced stability in Li–S batteries. However, to effectively design such polymers, a thorough understanding of the underlying redox mechanisms is critical. Here, we study electrochemical behavior of sulfur-rich copolymers using in operando FTIR spectroscopy with attenuated total reflection. We used sulfur-diisopropenylbenzene copolymers [poly­(S-co-DIB)] as the active m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
2
13
0
Order By: Relevance
“…9 The electrochemical behaviour of S-DIB cells was investigated using operando Fourier transform-infrared spectroscopy with attenuated total reflection (FTIR-ATR). 10 This study provided further evidence for C-S bonds remaining intact during battery operation, as well as a different discharge mechanism occurring in cathodes composed of high and low S-content copolymers, with little to no formation of higher order Li-polysulfides in the latter. The significantly higher cycle stability found for the low S-content polymer was attributed to this, and it was proposed that the shuttle effect may be successfully mitigated by keeping the S-strand length below 4.…”
Section: Introductionmentioning
confidence: 57%
“…9 The electrochemical behaviour of S-DIB cells was investigated using operando Fourier transform-infrared spectroscopy with attenuated total reflection (FTIR-ATR). 10 This study provided further evidence for C-S bonds remaining intact during battery operation, as well as a different discharge mechanism occurring in cathodes composed of high and low S-content copolymers, with little to no formation of higher order Li-polysulfides in the latter. The significantly higher cycle stability found for the low S-content polymer was attributed to this, and it was proposed that the shuttle effect may be successfully mitigated by keeping the S-strand length below 4.…”
Section: Introductionmentioning
confidence: 57%
“…As seen in the Fourier transform infrared spectra shown in Fig. 3c, a sharp peak at 1071 cm − 1 on behalf of the ν(S = O) band indicated the presence of sulfoxide (-S = O-) groups in the lms, 39 whereas only peaks related to the sulfur atom were found at 1255 cm − 1 and 694 cm − 1 , corresponding to Bi-S 40 or C-S 41 , respectively. That is, there were both sulfoxide (-S = O-) as well as a small amount of sulphone (-SO 2 -) bound to bismuth (III) ions in the original Bi-LCE lm.…”
Section: Resultsmentioning
confidence: 87%
“…In agreement with our theoretical prediction, the experimental measurements show that as the mass fraction of DIB increases (or similarly, as the average S chain length decreases), the Raman activity at around 473 cm −1 becomes less intensive. In a recent in operando FTIR study during discharge,36 it has also been observed that the characteristic S-S stretching vibration is absent in S/DIB copolymers containing short S n chains (n ≤ 4) throughout discharge. However, this peak evolves as a function of cell voltage in S/DIB copolymers with longer chains, clearly indicating the formation of different Li-polysulfides.In addition, in Fig.4we observe Raman activities at ∼165-200 cm −1 assigned to the sulfur chain deformation and S-S-S bending [see Fig.2(a) and (b)], which gradually disappear with increasing wt % of DIB (shorter sulfur chains).…”
mentioning
confidence: 89%
“…Therefore, a stable cycling for 1500 cycles has been reported. 36 This clearly emphasizes the need for a synthesis strategy which facilitates the formation of S/DIB copolymers with short sulfur chains in a controllable way. The present study shows that Raman spectroscopy is a powerful tool to investigate structural properties of S/DIB copolymers and provides a way to probe the…”
Section: The Comparison Of Quantum-chemical Calculations Of Raman Sig...mentioning
confidence: 99%